Are they necessary? Preventive therapies for post-stroke depression: A meta-analysis of RCTs. (February 2020) - Gu, Jiajie; Huang, Haoping; Chen, Kehua; Huang, Guanhua; Huang, Yuejun; Xu, Hongwu
Highlights: Prophylactic anti-depressive therapies following acute stroke were shown to reduce the incidence of depression in the patients. The effectiveness remained significant even in the follow-up period. Prophylactic anti-depressive therapies following acute stroke were shown to improve symptoms of depression, improve motor function and neurological function. The anti-depressive therapies showed no effects on mortality and adverse events incidence. Abstract: To explore the necessity and feasibility of early anti-depressive therapies in acute stroke patients, we conducted a meta-analysis of currently available randomized control studies (RCTs). Literature search in six databases was done with keywords of cerebrovascular accident, depression and prevention. Only RCTs that met the inclusion criteria were enrolled for further analysis. Twelve eligible studies were included in this meta-analysis. Prophylactic anti-depressive therapies following acute stroke were shown to reduce the incidence of depression in the patients (RR = =0.33, 95% CI: 0.25 to 0.43, p < 0.001), improve symptoms of depression (WMD: 5.73, 95% CI: 4.18 to 7.29, p < 0.001), improve motor function (WMD: 12.56, 95%CI: 9.07 to 16.04, p < 0.001) and neurological function (WMD: 1.13, 95%CI: 0.57 to 1.69, p < 0.001). However, anti-depressive therapies showed no effects on mortality (RR = 1.63, 95%CI: 0.55 to 4.85, p = 0.377) and adverse events incidence (RR = 0.93, 95%CI: 0.53 to 1.64, p = 0.806). Anti-depressive therapies following acute stroke is effective thus deserves to be advocated.